2022
DOI: 10.1002/admt.202200387
|View full text |Cite
|
Sign up to set email alerts
|

Superrepellent Doubly Reentrant Geometry Promotes Antibiofouling and Prevention of Coronavirus Contamination

Abstract: The fomite transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has drawn attention because of its highly contagious nature. Therefore, surfaces that can prevent coronavirus contamination are an urgent and unmet need during the coronavirus disease 2019 (COVID‐19) pandemic. Conventional surfaces are usually based on superhydrophobic or antiviral coatings. However, these coatings may be dysfunctional because of biofouling, which is the undesired adhesion of biomolecules. A superhydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The superhydrophobic surfaces that do not require the coating of additional materials for antimicrobial purposes have significant potential for industrial applications owing to their long service lives and lower structural limitations (owing to the absence of a coating). A notable example is the double reentrant topology (DRT) surfaces that possess anti-biofouling properties and antibacterial adhesion effects (Lee et al, 2022) [ 155 ]. A DRT is a structure with a negative sidewall angle, such as in mushrooms or umbrellas ( Figure 4 b).…”
Section: Anti-biofouling Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The superhydrophobic surfaces that do not require the coating of additional materials for antimicrobial purposes have significant potential for industrial applications owing to their long service lives and lower structural limitations (owing to the absence of a coating). A notable example is the double reentrant topology (DRT) surfaces that possess anti-biofouling properties and antibacterial adhesion effects (Lee et al, 2022) [ 155 ]. A DRT is a structure with a negative sidewall angle, such as in mushrooms or umbrellas ( Figure 4 b).…”
Section: Anti-biofouling Surfacementioning
confidence: 99%
“…Unlike other superhydrophobic surfaces, DRT does not require the use of low-surface-energy materials to achieve superhydrophobicity, relying on its special structure [ 156 ]. In a study by Lee et al (2022), DRT surfaces were observed to remain superhydrophobic and exhibit low microbial adhesion behaviors, even when hydrophilic and microbe adhesive materials (SiO 2 ) were used as contact materials [ 155 ]. The DRT surfaces can be considered mechanical anti-biofouling surfaces and may serve as an example that inspires the development of novel antibacterial surfaces.…”
Section: Anti-biofouling Surfacementioning
confidence: 99%